The resistance and resilience of European beech seedlings to drought stress during the period of leaf development - Gebauer, Roman; Plichta, Roman; Urban, Josef; Volařík, Daniel; Hájíčková, Martina (Tree physiology, 2020)
Spring drought is becoming a frequently occurring stress factor in temperate forests. However, the understanding of tree resistance and resilience to the spring drought remains insufficient. In this study, European beech (Fagus sylvatica L.) seedlings at the early stage of leaf development were moderately and severely drought stressed for 1 month and then subjected to a 2-week recovery period after rewatering. The study aimed to disentangle the complex relationships between leaf gas exchange, vascular anatomy, tree morphology and patterns of biomass allocation. Stomatal conductance decreased by 80 and 85% upon moderate and severe drought stress, respectively, which brought about a decline in net photosynthesis. However, drought did not affect the indices of slow chlorophyll fluorescence, indicating no permanent damage to the light part of the photosynthetic apparatus. Stem hydraulic conductivity decreased by more than 92% at both drought levels. Consequently, the cambial activity of stressed seedlings declined, which led to lower stem biomass, reduced tree ring width and a lower number of vessels in the current tree ring, these latter also with smaller dimensions. In contrast, the petiole structure was not affected, but at the cost of reduced leaf biomass. Root biomass was reduced only by severe drought. After rewatering, the recovery of gas exchange and regrowth of the current tree ring were observed, all delayed by several days and by lower magnitudes in severely stressed seedlings. The reduced stem hydraulic conductivity inhibited the recovery of gas exchange, but xylem function started to recover by regrowth and refilling of embolized vessels. Despite the damage to conductive xylem, no mortality occurred. These results suggest the low resistance but high resilience of European beech to spring drought. Nevertheless, beech resilience could be weakened if the period between drought events is short, as the recovery of severely stressed seedlings took longer than 14 days.
Keywords: Photosynthesis; embolism; Plant Leaves; net photosynthesis; stomatal conductance; hydraulic conductivity; Water; období sucha; Droughts; vascular anatomy; fotosyntéza; Seedlings; Fagus; buk (rod); semenáček; voda; listy rostlin; chlorophyll fluorescence